2018
DOI: 10.4103/1319-2442.239629
|View full text |Cite
|
Sign up to set email alerts
|

The burden of caring for renal patients: The nurses perspective

Abstract: Prevalence of chronic kidney disease (CKD) in Nigeria is on the increase and it is associated with increasing caregiving burden for both the professionals and informal caregivers. This study evaluated the burden experienced by nurses caring for CKD patients, identified the procedures causing the caregiving burden and factors associated with burden in two hospitals in Ondo State, Nigeria. Two hundred and forty nurses caring for renal patients were selected from two health institutions in Ondo State. Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Contrary to the results of the present study, the results of the study by Rioux et al showed low levels of burden among hemodialysis caregivers, which can be attributed to some factors, such as nocturnal dialysis at home, independency and the ability of most patients to self-care with highly educated caregivers (29). Studies have shown that caregivers of patients suffer greatly from various physical, mental, emotional, social and economical dimensions (26). Recent studies have also shown that home caregivers, (29,30).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the results of the present study, the results of the study by Rioux et al showed low levels of burden among hemodialysis caregivers, which can be attributed to some factors, such as nocturnal dialysis at home, independency and the ability of most patients to self-care with highly educated caregivers (29). Studies have shown that caregivers of patients suffer greatly from various physical, mental, emotional, social and economical dimensions (26). Recent studies have also shown that home caregivers, (29,30).…”
Section: Discussioncontrasting
confidence: 99%
“…The study of Alnazly et al among Jordanian caregivers showed that most of caregivers (76%) experienced severe level of burden (25). However, Mobolaji et al reported that (48.3%) of hemodialysis patients' caregivers in Nigeria experienced mild-to-moderate burden, (10.4%) experienced severe burden while only (1.3%) experienced very severe burden (26). Similarly, the result of the study by Nagarathnam et al showed, a higher percentage of caregivers (85%) had mild to moderate burden (27).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of moral distress has not been well studied in nephrology and even less in SSA [ 57 ]. A study among nurses who manage patients with chronic kidney disease in 2 major hospitals in Nigeria found that the burden of care, as measured by the Zarit Burden of Life Instrument, was highest for dialysis [ 58 ]. Leading factors which contributed to the higher burden of care in dialysis included staff shortages, patients’ lack of funds and difficulty finding kidney donors, closely followed by erratic power and water supplies, lack of equipment, patient mal-adherence and patients’ inability to sustain dialysis.…”
Section: Discussionmentioning
confidence: 99%